Negotiating Toilet Access: A Qualitative Exploration of Women's Incarceration. (June 2023) - Smoyer, Amy B.; Schwarz, Paige; Camenga, Deepa; Rickey, Leslie
Norms and behaviors about toileting in prison can expand understanding of women's lived experience of incarceration. Knowledge about this subject is significant because access to clean, safe toilets is a human rights issue, and toilet habits can impact social, mental, and physical outcomes. Three focus groups were conducted with 15 incarcerated women about their quotidian prison toilet experiences. While the toilet was physically available, institutional regulations, social norms, and women's individual psychologies limited their access and utilization. The ways in which toilet use was negotiated with self, peers, and are described, and the implications of these findings are discussed.